1999
DOI: 10.1159/000007194
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activities of Meropenem and Other Antimicrobial Agents against British Meningococcal Isolates

Abstract: The in vitro activity of meropenem was compared with those of penicillin, ampicillin, cefuroxime, cetriaxone, cefotaxime, rifampicin, chloramphenicol, sulphadiazine and ciprofloxacin against 121 British meningococcal isolates by a microdilution method in Mueller-Hinton broth and by the E test. All meningococcal strains were susceptible to the agents except for ampicillin (88.4%), penicillin (88.4%), sulphadiazine (57.9%) and rifampicin (95%). The emergence of resistance problems among meningococcal isolates st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In most of these reports few isolates of the bacterium have been studied and the clinical response to therapy was considered as adequate for detecting susceptibility. Penicillin has traditionally been recognized as the antibiotic of choice but in recent years reports of resistance of meningococci to penicillin have been noted, although the frequency with which such resistant isolates are found varies widely [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…In most of these reports few isolates of the bacterium have been studied and the clinical response to therapy was considered as adequate for detecting susceptibility. Penicillin has traditionally been recognized as the antibiotic of choice but in recent years reports of resistance of meningococci to penicillin have been noted, although the frequency with which such resistant isolates are found varies widely [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that these chromosomal alterations have been transferred among N. meningitidis serogroups and among other Neisseria species [26]. In one British study [27], 42% of meningococcal isolates were resistant to sulfadiazine.…”
Section: Neisseria Meningitidismentioning
confidence: 99%
“…In 1997, active population-based surveillance in the United States found approximately 3% of clinical isolates to be of intermediate resistance; this value had not increased since 1991 [29]. High-level chloramphenicol resistance (MIC 64 µg/ml) was described recently in Vietnam and France [30]; in one European study, the prevalence of isolates resistant to rifampin was reported as 5% [27]; in the US, the prevalence has been reported to be 3% [29].…”
Section: Neisseria Meningitidismentioning
confidence: 99%